A cross-sectional study on the associations of insulin resistance with sex hormone, abnormal lipid metabolism in T2DM and IGT patients. Issue 26 (June 2017) - Wang, Xiaoxia; Xian, Tongzhang; Jia, Xiaofan; Zhang, Lina; Liu, Li; Man, Fuli; Zhang, Xianbo; Zhang, Jie; Pan, Qi; Guo, Lixin
Abstract : Abstract: Type 2 diabetes mellitus (T2DM) is a long-term metabolic disorder. It is characterized by hyperglycemia, insulin resistance (IR), and relative impairment in insulin secretion. IR plays a major role in the pathogenesis of T2DM. Many previous studies have investigated the relationship between estrogen, androgen, and obesity, but few focused on the relationship between sex hormones, abnormal lipid metabolism, and IR. The goal for the present study was to identify the association of IR with sex hormone, abnormal lipid metabolism in type 2 diabetes, and impaired glucose tolerance (IGT) patients. In total 13, 400 participants were analyzed based on the results of the glucose tolerance test. Using a cross-sectional study, we showed the relationship between IR and the level of sex hormones among 3 different glucose tolerance states: normal control people, IGT, and T2DM patients. We also analyzed the relationship between IR and abnormal lipid metabolism. Significantly, luteinizing, progesterone, estradiol, prolactin, and follicle-stimulating hormone levels decreased in T2DM and IGT patients compared with those in normal control people. The association between IR and lipid metabolism disorders in T2DM and IGT patients was also observed. Our clinical findings may offer new insights into understanding the mechanism of metabolic disorders and in new therapeutic methods for the treatment of the prevalence of type 2 diabetes.